Impact of Behavioral Issues on Green Growth Policies and Weather-Related Disaster Reduction in Developing Countries - Kunreuther, Howard; Michel-Kerjan, Erwann (World Bank, Washington, DC, 2013)
This paper focuses on how developing countries can change the way they prepare for disasters so they are better equipped to sustain economic growth. It discusses the importance of considering the goals of key decision makers and the need to understand the perceptions, systematics biases, and heuristics used by the relevant interested parties (the affected public, private and public sector organizations, and nongovernmental organizations) in choosing between alternatives. The paper highlights the importance of undertaking benefit-cost analysis to evaluate disaster risk reduction measures, recognizing that decision makers might not make meaningful use of this policy tool given their behavioral biases and simplified heuristics. To address these issues, the authors propose green growth strategies that involve multi-year contracts coupled with short-term incentives that have a chance of being implemented. The strategies focus on the role of multi-year micro-insurance, long-term loans, and multi-year catastrophe bonds that reflect the institutional arrangements in the developing country. The paper illustrates this proposal in the case of farmers' agricultural practices and investment decisions that reduce losses to property from catastrophic disasters such as drought.